Maternal exposure to PM2.5 may increase the risk of congenital hypothyroidism in the offspring: a national database based study in China. - Shang, Li.; Huang, Liyan.; Yang, Wenfang.; Qi, Cuifang.; Yang, Liren.; Xin, Juan.; Wang, Shanshan.; Li, Danyang.; Wang, Baozhu.; Zeng, Lingxia.; Chung, Mei Chun. (Tufts University. Tisch Library., 2019)
Keywords: Particulate matter, Air quality index, Congenital hypothyroidism, Cut-off value.; Springer Open.